Evaluasi Kompetensi Lulusan Program Studi Pendidikan Guru Pendidikan Anak Usia Dini Universitas Nusantara PGRI Kediri - Widi Wulansari; Epritha Kurniawati; Linda Dwiyanti (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2017)
Competence evaluation is conducted to see how much ability and expertise possessed by graduates from PG-PAUD UN PGRI Kediri study program in educating young children in accordance with the stage of development optimally. Based on the results of the evaluation can be used as a reference in improving and improving the quality of graduates of PG-PAUD UN PGRI Kediri in order to have high competitiveness in accordance with current technological developments and progress. This research is an evaluation research using consumer oriented evaluation model. The study was conducted in 20 kindergartens and Raudhatul Atfal in Kediri. Research subjects consisted of 20 principals and 40 teachers. Data collection was done by questionnaire method, and interview. The research instrument is validated based on expert judgment and trial. The data of the research were analyzed using descriptive statistics. The results showed that (1) the assessment of the four competencies, namely professional, personality, social, and pedagogic which is owned by PG-PAUD graduate of Universitas Nusantara PGRI Kediri in Kindergarten and Raudhatul Atfal (RA) . However, there is still a need for improvement and improvement on professional and pedagogic competence due to good category grading scores given by graduate users of less than 50%; (2) assessment of user satisfaction of PG-PAUD graduate of Universitas Nusantara PGRI Kediri is a satisfactory category for professional and social competence. While the category is very satisfying for personal and pedagogic competence.